Soil Monitoring and Crop Yield Prediction Using Machine Learning (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet of Things (IoT) is a quickly developing innovation and the field of IoT is broadening its wings in all of the zones today. With the movement in PCs like Arduino the advancement is accomplishing the ground level with its application in cultivating. In this work, we have illustrated and realized observing of soil quality by using Arduino, different Sensors and Android application. Soil quality boundaries utilized in this work are temperature, soil dampness level Ammonia and carbon content. Sensor securing is led by Arduino is utilized as information handling gadget just as worker. Android phone is utilized as the terminal gadget. To improve profitability of agribusiness through astute homestead the executives, the information breaking down should be very much investigated and handled ML calculations could be applied to additional upgrade application knowledge and usefulness. In this article we audit existing methodologies have been made to the savvy agribusiness and cultivating dependent on IoT and ML independently. Additionally, we propose novel ideas that how might ML-IoT can be mixed in such applications.